(untitled) (Management Dynamics, 2023)
Non-monetary incentives play a significant role in motivating employees and fostering a positive work environment. Initiatives to motivate and promote employees work-life have increasingly become prominence in Nepal’s banking industry. This study examines the impact of non-monetary incentives on employee motivation in the context of commercial banks in Kathmandu valley. Recognition, availability of responsibility, and career advancement opportunities, are taken as independent and employee motivation as a dependent variable of the study. The total population of the study are the total number of bankers in Kathmandu. However, only 120 bank employees (representing 66.67 response rate) from six commercial banks are taken as a sample purposively and given as uniform structured 5-points Likert type questionnaires through survey. In order to determine connections between study variables and to assess the impact, the collected data were examined using correlation coefficient and regression analysis. This study found significant positive impact on availability of responsibility and career advancement opportunities and no significant impact of recognition on employee motivation. Moreover, this study provides valuable insights for organizations seeking to improve employee motivation through non-monetary incentives. In addition, the results also provide bank management valuable insights to design effective strategies for employee motivation, ultimately leading to improved organizational performance and employee satisfaction.